Indonesia as Legal Welfare State: The Policy of Indonesian National Economic Law - Rian Saputra; Silaas Oghenemaro Emovwodo (Journal of Human Rights, Culture and Legal System, 2022)
The purpose of this study is to ascertain the relationship between investment law and state sovereignty, and then to construct national investment law politics in the future in order to advance economic development and retain independence. This research is normative by taking a statutory approach and a conceptual approach. The study's findings indicate that investment is critical for economic growth and job creation. Governments throughout the world are aggressively competing to improve the business climate and so encourage investment activities, but this competition should be controlled and emphasize domestic capital, as it signals to Indonesian state leaders that investment is a priority. While the contribution of foreign funds or foreign aid is not denied in developing Indonesia's declining economy, it must first rely on domestic capabilities as a source of development funds to ensure that the existence of foreign sources of funds does not result in dependence on foreign parties and that foreign heads of funds are used for the benefit of the people's economy.KeywordsPolicy;Economic Law;Welfare;